Experiencing Climate Change and Living Through It—Provocations for Education Based on South African Youth Experiences of Climate Change Policymaking and Politics - Tyler Booth; Harriet Thew (Youth)
This research investigates youth participation in climate change politics and policymaking in South Africa, responding to a notable lack of Global South-facing studies in the literature on youth climate activism. Guided by our lead author’s substantial engagement in South Africa’s youth climate movement from 2014–2024 and drawing upon semi-structured interviews with 12 young climate activists, we offer rich insights into young South Africans’ motivations to participate in climate politics and policymaking. We then draw upon these insights to offer a series of provocations for climate change education. On investigating why youth participate, we find that although they report similar intrinsic and extrinsic motivations for participation to their Global North counterparts, South African youth climate activists place far greater emphasis on situated awareness and lived experience. We further improve the understanding of how young people perceive meaningful participation and climate (in)justices and how this shapes and is shaped by their activism. We therefore emphasise the value of incorporating both local case studies and affective elements in climate change pedagogies to encourage participation in collective climate action. Ultimately, we call for an enhanced recognition and inclusion of youth as active contributors to, and educators within, climate change governance and for the reconceptualization of youth climate activism, and policy engagement as key sites of transformative learning.